Pengaruh Sikap, Norma Subjektif, dan Religiusitas Terhadap Preferensi Halal Pada Produk Kosmetik di kalangan Gen Z - Hakiki, Habibillah; Priantina, Anita (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
The aim of this study is to analyse the influence of attitudes, subjective norms and religiosity on halal preferences for cosmetic products, with a focus on Generation Z. Using a quantitative method with an SEM-PLS approach, this study collected primary data from Generation Z respondents who purchased halal cosmetic products. The analysis shows that attitudes, subjective norms and religiosity together have a significant influence on halal preferences, allowing a deeper understanding of the factors that influence purchasing decisions in this context. The findings of this study provide valuable insights for marketers of halal cosmetic products to develop more targeted and effective marketing strategies to reach Generation Z consumers. Nevertheless, this study has limitations, such as geographical restrictions and not taking into account certain external variables. Therefore, it is recommended for future research to expand the scope and consider additional external factors. To summarise, this study should provide a basis for developing smarter marketing strategies that address halal preferences in cosmetic products in the digital age.